2008
DOI: 10.1007/s10509-008-9856-x
|View full text |Cite
|
Sign up to set email alerts
|

Period changes and light curve analysis of eclipsing binary AB Andromedae

Abstract: BV photometry of close binary star AB And in two observational seasons have been presented. Updated O-C diagram analysis by Kalimeris method yielded the values of 0.0188 day and 0.0065 day as amplitudes of orbital period modulation with P mod1 ∼ 61 yr and P mod2 ∼ 34 yr as the modulation periodicities. Light curve analysis was carried out by W-D method and geometric and physical parameters of the components. Finally, the consequences of period changes have been discussed on the basis of light-time effect due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
(18 reference statements)
1
3
0
Order By: Relevance
“…Our work corrected claims made by Li et al (2014), because we found an error in their determination of times of minima type for the old data. The results of the present study are similar in some respects with the results of Hasanzadeh et al (2008): also in their paper there are two periodical modulations of the times of minima.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our work corrected claims made by Li et al (2014), because we found an error in their determination of times of minima type for the old data. The results of the present study are similar in some respects with the results of Hasanzadeh et al (2008): also in their paper there are two periodical modulations of the times of minima.…”
Section: Discussionsupporting
confidence: 90%
“…Their luminosity variation in long time scales was ∆(L 1 + L 2 ) = 0.18L ⊙ . Hasanzadeh et al (2008) attributed the second modulation of the orbital period to the magnetic mechanism. The possible causes of orbital period modulations can be (at least, in principle) clarified using future CCD photometry, radial velocity, astrometric and direct observations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A majority of contact binary stars are found to have changes in their periods with Ṗ evenly distributed around zero and up to ± 2.3 × 10 −7 day year −1 , indicating that decreasing periods are not favored (Kubiak et al 2006). Systems like AB Andromedae (Hasanzadeh et al 2008), AH Virgo, and V566 Ophiuchus vary in their eclipse times by up to 2 hr. V502 Ophiuchus (Kalimeris et al 1994) is a contact binary with a period of 0.4533925 days that shows a 40 minute change in its O-C times, quite similar to KIC 9832227.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…As regards the work of the first investigators, a first application was made to AB And [113], while many others followed by various researches among whom some are mentioned [117][118][119][120][121][122][123][124][125]. In the application to AB And [113], it is clearly shown that from two different (O-C) diagrams -constructed using two different ephemeris formulae-the same results come out for the orbital period changes of this system analysed with the continuous method proposed in [114].…”
Section: Ways Of An (O-c) Diagram Analysismentioning
confidence: 99%